(untitled) (ENTHYMEMA, 2025)
Sir Gawain and The Green Knight explores the transformation of Gawain’s identity through his quest, where time and space play crucial roles. The narrative juxtaposes brief, action-packed episodes with extended periods of stillness, emphasizing Gawain’s passive heroism. The circular structure of the journey symbolizes a return to the self, yet transformed through encounters with the other. The use of Paul Ricœur’s theory about narrative identity highlights the significance of Gawain’s wounds as paths to self-recognition. The comparison with David Lowery’s 2021 film adaptation reveals contemporary concerns with identity and otherness.